ANALYSIS DETERMINANTS OF TYPE 2 DIABETES MELLITUS: A CASE CONTROL STUDY: Analisis Determinan Kejadian Diabetes Mellitus Tipe 2: Studi Case Control - Sirait, Reni Aprinawaty; Hulu, Victor Trismanjaya; Sitorus, Rotua Sumihar; Susanti, Dewi; Handayani, Sri; Sinambela, Megawati; Rahmi, Nurfadhilah (Jurnal Berkala Epidemiologi, 2025)
Background: Type 2 Diabetes Mellitus (type 2 DM) is a chronic disease in adults due to the body's resistance to insulin. Purpose: This study aims to analyze the determinants of the incidence of type 2 DM. Methods: The study design was a case-control study. The case population in this study was patients with type 2 DM who had been diagnosed by doctors based on data available in the medical records of Bintang Bayu Health Center. In contrast, the control population was patients who did not suffer from type 2 DM. The study's sample size was 138 people, with a ratio of cases to controls of 1:2. The case group consisted of 46 people, and the control group comprised 92 people. The sampling technique used was nonprobability sampling, namely, consecutive sampling. Questionnaire distribution was the primary method of data collection. The frequency distribution of each variable was calculated before analyzing the data using Chi-square and logistic regression. Results: Diet (p=0.001; OR=4.7; 2.231–10.154), knowledge (p=0.033; OR=2.3; 1.129–4.785), physical activity p = 0.010; OR = 2.8; 1.342 – 6.032), hypertension (p=<0.001; OR=4.9; 2.089–11.784) were significant to the incidence of type 2 DM. The most dominant variable was hypertension, p=<0.001; OR=7.3 (2.581-20.680). Conclusions: Poor diet, poor knowledge, light physical activity, and hypertension were significant factors in the incidence of type 2 DM.